Green Accounting Based Tabligh at Sugar Factory in Indonesia - Hanafie, Hadriana; Utari, Emy; Manrimawagau Bayan, Andi Yustika; Abdullah, Muhammad Wahyuddin (Technium Social Sciences Journal, 2023)
The purpose of this research is to determine the reporting of environmental costs as green accounting based tabligh that applied to sugar factories. This research is a qualitative research using an interpretive phenomenological approach. The source of data in this study is primary data obtained from informants and secondary data using other literature. This research was conducted at PT Perkebunan Nusantara XIV is a sugar factory located in Pa’rappunganta Village, North Podbangkeng district, Takalar Regency, Indonesia. The data analysis techniques used in this study are data reduction, data presentation and drawing conclusions/verification. The results of this study show that PTPN XIV Takalar Sugar Factory has incurred environmental costs. However, these costs have not been grouped by category, but are only grouped in one cost post on the annual financial statement, namely waste prevention costs. This sugar factory has not fully met the cost elements of environmental cost reporting and sustainable reporting.